Experimental research on dynamic response of capacity control system in reciprocating compressor. (February 2014) - Yuanyang, Zhao; Bin, Tang; Guangbin, Liu; Liansheng, Li; Huaide, Yang; Wenhui, Meng; Feng, Zhu; Haiping, Xu
The forces acting on the actuator used in a reciprocating capacity control system are analyzed in this article. The dynamic response of this system is influenced significantly by hydraulic pressure and reset spring force. The performance of dynamic response is tested under different hydraulic pressures and reset springs. The results show that the influence of reset spring force on the downward speed and displacement of actuator is more inconspicuous than the hydraulic pressure, but the reset speeds decrease obviously when the reset spring force is small (SPR2 and SPR3). The maximum downward displacement decreases and the consuming time increases with the decrease in the hydraulic pressure. The maximum downward speed of actuator decreases with the decrease in hydraulic pressure which influences the reliability and life of this system. Therefore, the performance of dynamic response and operating lifetime needs to be considered simultaneously during the design of partial stroke press-off inlet valve capacity control systems.